Penguatan UMKM Simpang Sender melalui Pelatihan Manajerial bagi Para Pelaku Usaha - Novalia, Nurkardina; Kurniawan, Muhammad; Sudiyanto, Totok; Mursalin, Mursalin; Suhada, Suhada; Puspita, Santi (Penerbit Goodwood, 2024)
Purpose: The specific objective to be achieved in this service activity is to assist MSMEs in Simpang Sender Village e in strengthening business legality, so as to increase competitiveness. Methodology: The method used as an approach to implementing community service is service and assistance in meeting needs through service assistance and education. The series of methods used consisted of lectures, demonstrations, and mentoring. Results: The implementation of community service activities in Simpang Sender Village received high enthusiasm from MSME players and involved support from the Village Head, community participation, enthusiasm of the participants, and assistance by the service team. On the other hand, the obstacles in this activity involve limited training time and distance, as well as obstacles in training follow-up. The positive impact of this activity involves increased knowledge about ICT-Based Business Legality, increased interest in entrepreneurship, and a forum for marketing products through Digital Marketing. Conclusions: The management training provided for MSMEs has had a positive impact. The training has successfully improved the entrepreneurs' ability to develop business plans and management strategies. It is hoped that the knowledge and experience shared by the speakers and the service team during the training will serve as a strategic guide for entrepreneurs in formulating business plans as a foundation for business development. Limitation: This research only focuses on Community Service (PKM) participants in the form of Micro, Small and Medium Enterprises (MSMEs) in Simpang Sender Village, Buay Pematang Sub-district, Ranau Tengah Regency, OKU Selatan. Contribution: Contribute in the form of knowledge and experience to MSME actors in accordance with their fields of competence. Knowledge such as marketing their products through various digital platforms, such as social media, marketplaces, websites, emails, and forums.